Protection of Victims of Sexual Violence in Higher Education based on a Progressive Legal Perspective - Mohammad Hanifal Fatahillah R Jantu (Estudiante Law Journal, 2023)
The purpose of this study is to analyze the protection of victims of sexual violence in higher education based on a progressive legal perspective. This type of research method is legal research that is normative in nature using a statutory approach and a case approach. The analysis used is Descriptive data analysis with a qualitative approach to secondary data and primary data. The results of this study show that there is progressiveness to provide comprehensive protection for victims of sexual harassment or violence in higher education. This is evidenced by the implementation of the Permendikbud ristek number 30 of 2021 concerning the prevention and handling of sexual violence in universities which is a legal umbrella that is more exclusive than the Criminal Code in resolving sexual violence on campus because victim protection based on the Criminal Code, only focuses on sanctions of perpetrators without rigid protection of victims, while the Minister of Education and Culture Ristek,   The rights of victims are made a priority, which is certainly in line with progressive laws that prioritize legal recensorship according to the times.